Design of alginate nanoparticles as oral insulin carrier / Aminah Kadir - Kadir, Aminah (2015)
The relationship of high and low molecular weight mannuronic acid (M)- and guluronic acid (G)-rich alginate nanoparticles as oral insulin carrier was elucidated. Nanoparticles were prepared through ionotropic gelation using Ca2 +, and then in vitro physicochemical attributes and in vivo antidiabetic characteristics were examined. The alginate nanoparticles had insulin release retarded when the matrices had high alginate-to-insulin ratio or strong alginate-insulin interaction via O-H moiety. High molecular weight M-rich alginate nanoparticles were characterized by assemblies of long polymer chains that enabled insulin encapsulation with weaker polymer-drug interaction than nanoparticles prepared from other alginate grades. They were able to encapsulate and yet release and have insulin absorbed into systemic circulation, thereby lowering rat blood glucose. High molecular weight G- and low molecular weight M-rich alginate nanoparticles showed remarkable polymer-insulin interaction. This retarded the drug release and negated its absorption. Blood glucose lowering was, however, demonstrated in vivo with insulin-free matrices of these nanoparticles because of the strong alginate-glucose binding that led to intestinal glucose retention. Alginate nanoparticles can be used as oral insulin carrier or glucose binder in the treatment of diabetes as a function of its chemical composition. High molecular weight M-rich alginate nanoparticles are a suitable vehicle for future development into oral insulin carrier